2005
DOI: 10.1088/0957-4484/16/2/021
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-enhanced growth and optical properties of ZnO nanowires grown on porous silicon substrates

Abstract: ZnO nanowires have been synthesized on porous silicon substrates with different porosities via the vapour-liquid-solid method. The texture coefficient analysed from the XRD spectra indicates that the nanowires are more highly orientated on the appropriate porosity of porous silicon substrate than on the smooth surface of silicon. The Raman spectrum reveals the high quality of the ZnO nanowires. From the temperature-dependent photoluminescence spectra, we deduced the activation energies of free and bound excito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 23 publications
3
62
0
Order By: Relevance
“…Two prominent peaks at 330 and 436 cm À1 originate from the 2E 2 mode and nonpolar optical phonon mode (E 2 ), respectively. 24,25 The high intensity nonpolar The presence of oxygen decient nanowires because of Fe ion incorporation is also conrmed by the existence of corresponding vibration modes as indicated in the Fig. 2(b), which is consistent with earlier reported results.…”
supporting
confidence: 90%
“…Two prominent peaks at 330 and 436 cm À1 originate from the 2E 2 mode and nonpolar optical phonon mode (E 2 ), respectively. 24,25 The high intensity nonpolar The presence of oxygen decient nanowires because of Fe ion incorporation is also conrmed by the existence of corresponding vibration modes as indicated in the Fig. 2(b), which is consistent with earlier reported results.…”
supporting
confidence: 90%
“…This observation shows that the growth behaviour of the ZnO NWs on the Si substrate is quite different from that of the ZnO NWs on the GaN/sapphire substrate. The reason can be attributed to the large differences in their thermal expansion coefficients, lattice mismatch and difference in crystal structure cause a rather large stress between ZnO and Si substrate [24,25]. On the other hand, it was found that, due to higher rate of nucleation on the Si substrate, the surface density of nucleation centres was very high [26] and incompatibility of the lattice structure between the cubic Si substrate and the hexagonal ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…Peak of (100), (002), (101), (102) and (110) correspond to hexagonal ZnO wurtzite can be observed apparently (JCPDS No: 36-1451). Besides, peak of impurity corresponds to silicon was also appeared in between of plane (100) and (002), located at ~33.2° for all samples (JCPDS No: 17-0901) [21,22]. Fig.…”
Section: International Integrated Engineering Summit 2014mentioning
confidence: 99%